Determination of ZNHD based on GPS Data, Radiosonde, and Numerical Weather Model - Susilo, Susilo; D. Wijaya, Dudy; Kuntjoro, Wedyanto; Efendi, Joni (Indonesian Journal of Geospatial, 2012)
Abstract. Water vapor is a principal element in the thermodynamics of the atmosphere and plays an important role in clouds condensation, which eventually can affect the radiative energy balance. Water vapor cobservation is essential for monitoring global/regional scale of weather and climate changes. However, high variation of water vapor concentrations makes it difficult to observe accurately using the conventional meteorogical observation technique (radiosonde), which is limited in both space and time. Nowadays, accurate observation of water vapor can be accomplished by the Global Positioning System (GPS). In this research, we use 14 continuous GPS stations from Bakosurtanal to observe temporal characteristic of water vapor concentration over West Java region.Keywords: GPS, NCEP, radiosonde, topographic, ZNHD